2021
DOI: 10.3390/ijms22105403
|View full text |Cite
|
Sign up to set email alerts
|

Early-Pregnancy Dydrogesterone Supplementation Mimicking Luteal-Phase Support in ART Patients Did Not Provoke Major Reproductive Disorders in Pregnant Mice and Their Progeny

Abstract: Progestogens are frequently administered during early pregnancy to patients undergoing assisted reproductive techniques (ART) to overcome progesterone deficits following ART procedures. Orally administered dydrogesterone (DG) shows equal efficacy to other progestogens with a higher level of patient compliance. However, potential harmful effects of DG on critical pregnancy processes and on the health of the progeny are not yet completely ruled out. We treated pregnant mice with DG in the mode, duration, and dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In recent years, it has been gradually favored by clinicians and patients, and it is recognized as a safe and effective progesterone drug. Yongchuan et al observed the effect of 90 perimenopausal AUB patients treated with dydrogesterone tablets after TCRE [ 7 ]. The results indicated that the curative effect of the observation group was better compared to the control group treated with TCRE only, and the difference exhibited statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been gradually favored by clinicians and patients, and it is recognized as a safe and effective progesterone drug. Yongchuan et al observed the effect of 90 perimenopausal AUB patients treated with dydrogesterone tablets after TCRE [ 7 ]. The results indicated that the curative effect of the observation group was better compared to the control group treated with TCRE only, and the difference exhibited statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating dydrogesterone into these protocols helps create an optimal environment for embryo implantation and early pregnancy development. By extending and supporting the luteal phase, dydrogesterone is critical in maintaining endometrial receptivity, a pivotal factor in ART success [ 74 ].…”
Section: Reviewmentioning
confidence: 99%
“…[4,5] At present, the clinical treatment of TM mainly uses progestogen products, dydrogesterone belongs to the progestogen drugs, is the treatment of early threatened abortion drugs commonly used, and can increase the level of pregnant women's blood progesterone. [6][7][8] However, there are some disputes on the medical treatment of threatened abortion. For example, there is no accurate and appropriate method to judge the luteal function, and there are also differences in whether progesterone injection is effective.…”
Section: Introductionmentioning
confidence: 99%